The Verbal System of Classical Hebrew in the Joseph Story: An Approach from Discourse Analysis - Endō, Yoshinobu (Tyndale bulletin, 1993)
A dissertation investigating the function of the verbal forms in biblical Hebrew prose, focusing on the Joseph story and examining word order, tense, aspect, clause type, sequentiality, and related matters.